The Effect of Activating Schemata in Pre-Reading Activity on Students’ Reading Comprehension at MAN Koto Baru Padang Panjang - Fajrilhuda Yuniko (STBA Prayoga Padang, 2020)
Abstract This study was aimed to determine the extent of the effect of activating schemata in pre-reading activities on reading comprehension of the tenth class at MAN Koto Baru Padang Panjang. This research was an experimental study in which there were two groups given different treatments. The experimental group was taught by activating schemata in pre-reading activities while the control group was taught with conventional strategies or without activating schemata in pre-reading activities. Both groups were taught with the same material, teacher, and time allocation. To gather the research data, a reading comprehension test was used as an instrument. The findings of this study indicated that the score of the experimental group was better than the control group. It can be seen from the average score of the two groups; the average score of the experimental group was 67.88, while the average score of the control group was 60.00. The data were also analyzed by using statistical analysis. It was found that students ' scores taught by activating schemata in pre-reading activities and students' scores taught by using conventional strategies or without activating schemata in pre-reading activities had significant differences. The analysis of the t-formula showed that t-count (3.88) was higher than the t-table (2.00) with a significance level of 0.05. It showed that students taught by activating schemata in pre-reading activities had better reading comprehension skills than students taught using conventional strategies or without activating schemata in pre-reading activities in class X at MAN Koto Baru Padang Panjang.